A Macroeconomic Model with Financial Panics - Gertler, Mark; Kiyotaki, Nobuhiro; Prestipino, Andrea (Review of Economic Studies, 2020)
Abstract This article incorporates banks and banking panics within a conventional macroeconomic framework to analyse the dynamics of a financial crisis of the kind recently experienced. We are particularly interested in characterizing the sudden and discrete nature of banking panics as well as the circumstances that make an economy vulnerable to such panics in some instances but not in others. Having a conventional macroeconomic model allows us to study the channels by which the crisis affects real activity both qualitatively and quantitatively. In addition to modelling the financial collapse, we also introduce a belief driven credit boom that increases the susceptibility of the economy to a disruptive banking panic.